2005
DOI: 10.1042/bj20041670
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adenylate cyclase type VIII splice variants by acute and chronic Gi/o-coupled receptor activation

Abstract: We previously reported that acute agonist activation of G(i/o)-coupled receptors inhibits adenylate cyclase (AC) type VIII activity, whereas agonist withdrawal following chronic activation of these receptors induces AC-VIII superactivation. Three splice variants of AC-VIII have been identified, which are called AC-VIII-A, -B and -C (with AC-VIII-B missing the glycosylation domain and AC-VIII-C lacking most of the C1b area). We report here that AC-VIII-A and -B, but not -C, are inhibited by acute mu-opioid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…We found that Gi/o plays a role in the action potential-independent GABA release in CeA, as PTX pre-treatment reduced the mean frequencies of mIPSCs in the CeA neurons from morphine WD rats but had no effects in placebo rats. This concurs with studies in cultured cell lines showing opioid-induced adenylyl cyclase superactivation that was sensitive to PTX treatment, implicating the involvement of PTX-sensitive Gi/o proteins in mediating these adaptive responses (Tso and Wong, 2000 ; Steiner et al, 2005 ). Another possibility may include a PTX-pretreatment induced substitution of Gi/o by Gz.…”
Section: Discussionsupporting
confidence: 86%
“…We found that Gi/o plays a role in the action potential-independent GABA release in CeA, as PTX pre-treatment reduced the mean frequencies of mIPSCs in the CeA neurons from morphine WD rats but had no effects in placebo rats. This concurs with studies in cultured cell lines showing opioid-induced adenylyl cyclase superactivation that was sensitive to PTX treatment, implicating the involvement of PTX-sensitive Gi/o proteins in mediating these adaptive responses (Tso and Wong, 2000 ; Steiner et al, 2005 ). Another possibility may include a PTX-pretreatment induced substitution of Gi/o by Gz.…”
Section: Discussionsupporting
confidence: 86%
“…Acute exposure to agonists of G i/o -coupled receptors—such as MOR, m 4 (muscarinic type 4), D 2 (dopaminergic type 2), and CB 1 (cannabinoid type 1) receptors—inhibits the activity of AC types I, V, VI, and VIII, while stimulating the activity of AC types II, IV, and VII [ 25 , 52 ]. Furthermore, acute activation of G i/o -coupled receptors leads to inhibition of AC-VIII-A and -B, but not of the AC-VIII-C splice variant in COS-7 cells transfected with MOR [ 53 ]. It would be interesting to investigate whether the cells coexpressing MOR and ORL1 utilize the same mechanism to regulate AC activity as well.…”
Section: Discussionmentioning
confidence: 99%
“…The close correlation between down-regulation of G␤ and ACS in SH-SY5Y cells suggests a cause-and-effect relationship, although the precise mechanistic link remains to be determined. However, from a knowledge that AC1 and AC8 mRNA is present in neuroblastoma cells (Jang and Juhnn, 2001) and that AC1 (Nielsen et al, 1996) and perhaps AC8 (Steiner et al, 2005) are inhibited by G␤␥, one possible mechanism whereby morphine sensitizes adenylate cyclase could be by the removal of a direct G␤␥-mediated inhibitory constraint. Indeed, this hypothetical mechanism may apply to the other morphine-sensitizable AC isoforms as well, because scavengers of G␤␥ were reported previously to block morphineinduced sensitization of AC5 and AC6 (Avidor-Reiss et al, 1996;Rubenzik et al, 2001), two AC isoforms also known to be inhibited by G␤␥ (Bayewitch et al, 1998).…”
mentioning
confidence: 99%